Absorption spectra peculiarities of thin films of (CsCu₂Cl₃)₁₋ₓ(CsCu₂l₃)ₓ system. - Yunakova, O.N.; Miloslavsky, V.K.; Kovalenko, E.N. (Functional Materials, 2004)
Absorption spectrum of (CsCu₂Cl₃)₁₋ₓ(CsCu₂l₃)x thin films has been investigated in the fundamental band region. The CsCu₂Cl₃ solid solutions have been found to be formed within the concentration ranges 0<x<0.08 and 0.34<x<1. In the 0.1<x<0.6 range, there is a mixture of two phases in the thin films, namely, of CsCu₂Cl₃-₃xI₃x solid solutions and CsCu₂Cl₃:Cu⁺. The latter phase appears as a result of a strong disordering of the CsCu₂Cl₃ anionic sublattice as Cl⁻ ions are substituted by l- ones having a larger radius. A new absorption band corresponds to that phase in the absorption spectrum peaked at 4.8 eV; it is associated with the excitation of quasi-impurity Cu⁺ ions in the cationic sublattice of the compound in the vicinity of l- ions. The concentration dependences of the exciton band position Eex(x) and half-width GA A A MA(x) are typical of solid solutions and confirm the formation thereof in the mentioned concentration ranges. Досліджєно спектр поглинання тонких плівок (CsCu₂Cl₃)₁₋ₓ(CsCu₂l₃)x у районі фундаментальної смуги. Встановлено, що тверді розчини CsCu₂Cl₃-₃xI₃x утворюються в інтервалі концентрацій 0<х<0,08 та 0,34<x<l. В інтервалі 0,l<x<0,6 у тонких плівках має місце суміш двох фаз: твердих розчинів CsCu₂Cl₃-₃xI₃x i CsCu₂Cl₃:Cu⁺. Фаза CsCu₂Cl₃:Cu+ виникає в результаті сильного розупорядкування аніонної підгратки CsCu₂Cl₃ при заміщенні іонів CI⁻ іонами більшого радіуса І-, їй відповідає в спектрі нова смуга поглинання при 4,8 еВ, позв’язана із збудженням квазідомішкових іонів Cu⁺ у катіонній підгратці з’єднання поблизу іонів І⁻. Концентраційні залежності положення Eex(x) і напівширини Г(х) екситонних смуг типові для твердих розчинів і підтверджують їхнє утворення у зазначених інтервалах концентрацій. Исследован спектр поглощения тонких пленок (CsCu₂Cl₃)₁₋ₓ (CsCu₂l₃)x в районе фундаментальной полосы. Установлено, что твердые растворы CsCu₂Cl₃-₃xI₃x образуются в интервале концентраций 0<x<0,08 и 0,34<x<1. В интервале 0,1<х<0,6 в тонких пленках имеет место смесь двух фаз: твердых растворов CsCu₂Cl₃-₃xI₃x u CsCu₂Cl₃:Cu⁺. Фаза CsCu₂Cl₃:Cu⁺ возникает в результате сильного разупорядочения анионной подрешетки CsCu₂Cl₃ при замещении ионов Cl⁻ ионами большего радиуса l⁻, ей соответствует в спектре новая полоса поглощения при 4,8 эВ, связанная с возбуждением квазипримесных ионов Cu⁺ в катионной подрешетке соединения в окрестности ионов l⁻. Концентрационные зависимости положения Eex(x) и полуширины Г(х) экситонных полос типичны для твердых растворов и подтверждают их образование в указанных интервалах концентраций.